2010
DOI: 10.1080/00288330.2010.515232
|View full text |Cite
|
Sign up to set email alerts
|

Diet and dietary variation of New Zealand hokiMacruronus novaezelandiae

Abstract: The diet of hoki was determined from examination of stomach contents of 1992 fish of 26Á112 cm total length (TL) sampled at depths of 209Á904 m on Chatham Rise, New Zealand, from summer research trawl surveys and seasonal commercial fishing trawls, during 2004Á2008. Prey was predominantly euphausiids, mesopelagic fishes and natant decapods. Multivariate analyses using distance-based linear models, non-parametric multi-dimensional scaling and similarity percentages indicated that the best predictors of diet var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…The subtropical front (STF) forms over Chatham Rise, where the mixing of subantarctic and subtropical water masses produces a region of heightened primary productivity [16], supporting abundant mesopelagic biomass [17]. Pronounced ecosystem changes across the STF on Chatham Rise have been correlated with changes in diet for several fish species [18][20], presumably because of variations in environmental conditions and prey availability.…”
Section: Introductionmentioning
confidence: 99%
“…The subtropical front (STF) forms over Chatham Rise, where the mixing of subantarctic and subtropical water masses produces a region of heightened primary productivity [16], supporting abundant mesopelagic biomass [17]. Pronounced ecosystem changes across the STF on Chatham Rise have been correlated with changes in diet for several fish species [18][20], presumably because of variations in environmental conditions and prey availability.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of SL over the number of stomachs with prey indicated that larger fish had higher proportion of empty stomachs. The decrease in the number of stomachs with prey in relation to fish size has been documented in mesopelagic fish and may be associated with a less frequent consumption in larger fish linked to a decrease in metabolic rate compared with smaller fish (Post and Lee 1996;Connell et al 2010;Dunn and Forman 2011). Another factor that could have influenced the absence of prey in larger fish would be related to the reproductive activity of P. tessellata.…”
Section: Effects Of Environmental Variables Body Size and Sex On Dietmentioning
confidence: 94%
“…1000 m (Leathwick et al ., ). The range of habitats (Leathwick et al ., ), and influence of the STF, is expected to provide a variety of foraging opportunities for demersal fishes, which could lead to substantial variability in feeding ecology (Connell et al ., ; Dunn et al ., ; Horn et al ., ; Stevens & Dunn, ).…”
Section: Introductionmentioning
confidence: 98%
“…In this study, the diets of A. niger, P. maculatus, N. rhomboidalis and H. atlanticus were examined on Chatham Rise, New Zealand. This research was part of a wider study of trophic structure in the fish assemblage on Chatham Rise, and part of a substantial variability in feeding ecology (Connell et al, 2010;Dunn et al, 2010;Horn et al, 2010;. 2011 (all four species), January 2012 (all species except H. atlanticus) and January 2014 (N. rhomboidalis only).…”
Section: Introductionmentioning
confidence: 99%